2007
DOI: 10.1093/annonc/mdl129
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary disease and targeted therapies for hematological malignancies—is the association real?

Abstract: During the past years targeted therapies have gained a major role in the treatment of cancer patients, including those with hematological malignancies. Extramedullary involvement is a rare manifestation of acute and chronic leukemias and of multiple myeloma. Nevertheless, with the expanding use of targeted treatments there is an impression that the incidence of extramedullary relapses is increasing. We reviewed the reports on this phenomenon in patients treated with all-trans-retinoic acid and arsenic trioxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 51 publications
2
37
0
Order By: Relevance
“…9 There have been numerous reports documenting increased extramedullary relapse and altered biological behavior following these therapies. 10,11 It is this environment of evolutionary pressure that is likely to engender the LEPP variant. In the context of targeted therapies, it is conceivable that LEPP represents a clonal expansion of those proliferative precursors that have not only acquired stromal independence but also lost the capacity to secrete IIG.…”
Section: Extramedullary Relapse Of Multiple Myeloma Associated With Amentioning
confidence: 99%
“…9 There have been numerous reports documenting increased extramedullary relapse and altered biological behavior following these therapies. 10,11 It is this environment of evolutionary pressure that is likely to engender the LEPP variant. In the context of targeted therapies, it is conceivable that LEPP represents a clonal expansion of those proliferative precursors that have not only acquired stromal independence but also lost the capacity to secrete IIG.…”
Section: Extramedullary Relapse Of Multiple Myeloma Associated With Amentioning
confidence: 99%
“…It has also been suggested that extramedullary relapse is more frequent in patients exposed to novel agents. 10 However, Varettoni et al 6 showed that previous exposure to bortezomid, thalidomide or lenalidomide was not associated to a higher risk of extramedullary relapse.…”
mentioning
confidence: 99%
“…Several reports describe the lack of sustained efficacy of thalidomide against EMD both at diagnosis and relapse. 13 However, thalidomide-based multiagent regimens have shown efficacy in EMD among patients who have experienced relapse who underwent allogeneic or ASCT. 13 Interestingly, bortezomib has proven efficacy in EMD in numerous case reports.…”
Section: Diagnosis In Oncologymentioning
confidence: 99%
“…13 However, thalidomide-based multiagent regimens have shown efficacy in EMD among patients who have experienced relapse who underwent allogeneic or ASCT. 13 Interestingly, bortezomib has proven efficacy in EMD in numerous case reports. 13 Ali et al 14 and Moriuchi et al 15 reported four cases in which bortezomib used as a single agent or with dexamethasone failed to achieve meaningful response in EMD, suggesting the importance of combination approaches with multiple agents.…”
Section: Diagnosis In Oncologymentioning
confidence: 99%
See 1 more Smart Citation